2021
DOI: 10.3389/fenvs.2021.737435
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Multidrug-Resistant Listeria monocytogenes in Environmental Waters: A Menace of Environmental and Public Health Concern

Abstract: The occurrence and antibiogram profiles of Listeria monocytogenes in environmental waters in the Eastern Cape Province, South Africa, were investigated. Seventy-eight samples from rivers, wastewater, and irrigation water were collected at different geographical locations within the province from February to September 2019. The procedure of the International Organization for Standardization EN ISO 11290:2017 part 1 and 2 was adopted for the isolation of Lm. The counts of presumptive Lm ranged from 2.0 × 103 CFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 64 publications
(97 reference statements)
0
18
1
Order By: Relevance
“…These virulence genes are linked to L. monocytogenes strains from clinical and food samples in Ireland (Poimenidou et al 2018 ), animals in Egypt (Elbar et al 2020 ), and the environment in South Africa (Iwu and Okoh 2020 ). Consistently, the rates of prfA and hly in L. monocytogenes strains obtained from environmental water in South Africa are high (Kayode et al 2021 ). Therefore, the presence of the virulence genes strongly suggested that L. monocytogenes strains from the studied dairy cattle farms could cause listeriosis in humans.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These virulence genes are linked to L. monocytogenes strains from clinical and food samples in Ireland (Poimenidou et al 2018 ), animals in Egypt (Elbar et al 2020 ), and the environment in South Africa (Iwu and Okoh 2020 ). Consistently, the rates of prfA and hly in L. monocytogenes strains obtained from environmental water in South Africa are high (Kayode et al 2021 ). Therefore, the presence of the virulence genes strongly suggested that L. monocytogenes strains from the studied dairy cattle farms could cause listeriosis in humans.…”
Section: Discussionmentioning
confidence: 79%
“…Tahoun et al ( 2017 ) reported high tetracycline, clindamycin, and rifampicin resistance in L. monocytogenes isolated from an Egyptian dairy farm. However, a previous investigation showed that L. monocytogenes isolated from environmental water has high resistance rates against sulfamethoxazole, oxytetracycline, and amoxicillin but not against ampicillin (Kayode et al 2021 ). These differences in the susceptibility patterns of L. monocytogenes strains could be dependent on geographical variations and antibiotic use for humans and animals.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the inlB gene (internalin B encoding gene) is linked to the strain’s ability to adhere to abiotic surfaces [ 34 ]. This gene was identified in all L. monocytogenes strains isolated from food as well as from the environment [ 6 , 31 , 35 ]. However, in certain studies, the prevalence is lower ( n = 15; 71.4%) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kayode et al [ 177 ] carried out in the United States confirmed high resistance to several groups of antimicrobials in L. monocytogenes strains isolated from the natural environment, surface water (rivers), wastewater, and irrigation water. Strains showed a high percentage of resistance to sulphonamides (sulfamethoxazole, STX) > 63.16%, tetracycline (oxytetracycline) 54.39%; β-lactams (amoxicillin) 50.88%, penicillin G 40.35%; aminoglycosides (streptomycin) 47.37%; cephalosporins (cefotetan) 45.61% and macrolides (erythromycin) 43.85%.…”
Section: Mechanisms Of Transfer Of Resistance Based On Examples Of Va...mentioning
confidence: 99%